Exploring the Potential of Cytochrome P450 CYP109B1 Catalyzed Regio—and Stereoselective Steroid Hydroxylation - Zhang, Xiaodong; Hu, Yun; Peng, Wei; Gao, Chenghua; Xing, Qiong; Wang, Binju; Li, Aitao (Frontiers in Chemistry, 2021)
Cytochrome P450 enzyme CYP109B1 is a versatile biocatalyst exhibiting hydroxylation activities towards various substrates. However, the regio- and stereoselective steroid hydroxylation by CYP109B1 is far less explored. In this study, the oxidizing activity of CYP109B1 is reconstituted by testing redox pairs from different sources, or by fusing it to the reductase domain of two self-sufficient P450 enzymes P450RhF and P450BM3 to generate the fused enzyme. The recombinant Escherichia coli containing necessary proteins are individually constructed for determining the steroid hydroxylation activity. The ferredoxin reductase (Fdr_0978) and ferredoxin (Fdx_1499) from Synechococcus elongates is found to be the best redox pair for CYP109B1, which gives above 99% conversion with 73% 15β selectivity for testosterone. By contrast, the rest ones and the fused enzymes show much less or negligible activity. With the aid of redox pair of Fdr_0978/Fdx_1499, CYP109B1 is used for transformation of different steroids. The results show that CYP109B1 displayed good to excellent activity and selectivity towards four testosterone derivatives, giving all 15β-hydroxylated steroids as main products except for 9(10)-dehydronandrolone. for which the selectivity is shifted to 16β. While for substrates bearing bulky substitutions at C17 position, the activity is essentially lost. Finally, the origin of activity and selectivity for CYP109B1 catalyzed steroid hydroxylation is revealed by computational analysis, thus providing theoretical basis for directed evolution to further improve its catalytic properties.